2022
DOI: 10.3390/cells11030472
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Profiling to Assess Signaling Changes upon VHL Restoration and Identify Putative VHL Substrates in Clear Cell Renal Cell Carcinoma Cell Lines

Abstract: The inactivation of von Hippel–Lindau (VHL) is critical for clear cell renal cell carcinoma (ccRCC) and VHL syndrome. VHL loss leads to the stabilization of hypoxia-inducible factor α (HIFα) and other substrate proteins, which, together, drive various tumor-promoting pathways. There is inadequate molecular characterization of VHL restoration in VHL-defective ccRCC cells. The identities of HIF-independent VHL substrates remain elusive. We reinstalled VHL expression in 786-O and performed transcriptome, proteome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…In terms of the biological activities of the dysregulated thrombus invasion-associated genes in our study, several in vitro experiments showed that TGFBI promoted adhesion, migration, and invasion in ccRCC cells (25,26). Recent study further showed that TGFBI were ubiquitinated and downregulated by VHL restoration and upregulated in human ccRCC (27). M2-related factor frequencies were regarded as robust biomarkers for predicting the renal clear cell carcinoma patient clinical phenotype and immune microenvironment.…”
Section: Discussionmentioning
confidence: 54%
“…In terms of the biological activities of the dysregulated thrombus invasion-associated genes in our study, several in vitro experiments showed that TGFBI promoted adhesion, migration, and invasion in ccRCC cells (25,26). Recent study further showed that TGFBI were ubiquitinated and downregulated by VHL restoration and upregulated in human ccRCC (27). M2-related factor frequencies were regarded as robust biomarkers for predicting the renal clear cell carcinoma patient clinical phenotype and immune microenvironment.…”
Section: Discussionmentioning
confidence: 54%
“…Research has indicated that polymorphisms in LUM are linked with the development and clinical manifestations of SLE (40). A study has confirmed that TGFBI serving as a ubiquitination substrate is reduced in clear cell renal cell carcinoma (ccRCC) (41). As a member of the collagen family, COL1A2 is significantly upregulated in metastatic ccRCC (42).…”
Section: Discussionmentioning
confidence: 99%
“…Many examples of multi-omics studies are available in literature, especially applied to biomarker discovery, such as Jiang et al for pancreatic cancer [ 130 ], Zheng et al for non-small cell lung cancer [ 131 ] and Buttacavoli et al for colon cancer [ 132 ]. Other studies extended from drug discovery, such as Sha et al for diabetic nephropathy [ 133 ] and Meng et al for chordoma [ 134 ], to the understanding of pathogenesis, as performed by Wang et al in clear cell renal cell carcinoma [ 135 ] and to the establishment of accessible databases of clinical and/or multi-omics data, as Answer ALS [ 136 ] or Fibromine [ 137 ]. Recently, this multi-omic approach has also been applied to the developing single-cell technology, as it could allow to capture multiple omic layers from the same cell.…”
Section: New Perspectivesmentioning
confidence: 99%